Perbandingan Kinerja Keuangan Bpr Sebelum Dan Sesudah Merger (Studi Kasus PT BPR Kita Centradana) - Paramitha Dewi, Made Prajna; Candradewi, Made Reina (Innovative: Journal Of Social Science Research, 2024)
The implementation of a bank merger is one of the attempts to avoid liquidation that could occur as a result of the worsening bank health condition. One of the Rural Bank that carried out the merger was PT BPR Dewata Indobank which merged with PT BPR Kita Centradana which is under the same PSP control. The implementation of the merger is expected to improve the financial performance of the synergies achieved. The purpose of this study is to analyze the difference in the financial performance of PT BPR Kita Centradana before and after merger measured by the ratio of LDR, Cash Ratio, DAR, CAR, ROA and BOPO. Data’s collected and interpolated into monthly data for analysis using descriptive statistics as well as normality test. Normal distributed data will be tested using paired sample t-test and abnormal distribute will be tested using Wilcoxon signed rank test. Based on the results of the research through the test of the hypothesis, there are significant differences in LDR, ROA and BOPO as well as no significant difference in the cash ratio, DAR and CAR. In general, the research results show that BPR Kita Centradana hasn’t fully achieved synergy in the short therm of eight months post merger. The management is expected to engage in strategic planning to make decisions capable of achieving synergie.